Pengembangan panduan konseling rational emotive behavioral teknik dispute cognitive untuk meningkatkan konsep diri dan resiliensi terhadap kemandirian pada siswa - Rusdayanti, I Gst. Agung Diah; Suarni, Ni Ketut; Dharsana, I Ketut; Dantes, Nyoman; Dharmayanti, Putu Ari (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2024)
Students who experience broken homes and have symptoms of self-injury behavior need to receive attention from the school in order to support self-concept and resilience towards independence in facing student’s problems. Guidance and counseling teachers' efforts to help students develop positive self-concept and resilience towards independence still experience obstacles due to limited facilities in the form of guidance modules that can assist in providing services. This research aims to compile and produce a design for a guidebook, determine the validity of the contents of the guidebook, determine the practicality of implementing the guidebook, and determine the effectiveness of implementing the rational emotive behavioral counseling guidebook, cognitive dispute techniques to increase self-concept and resilience towards independence in students. This research method uses research and development with a 4D development model. The results of this research are (1) the design of this counseling guidebook consists of five chapters, (2) the content validity of the guidebook is declared valid with a Content Validity Index of 0.8825 so that it has the feasibility of being developed and implemented by counseling guidance teachers for students, (3) the practicality of this guidebook is stated to be very practical for use by guidance and counseling teachers with an average result of 96.25%, (4) the implementation of the rational emotive behavioral counseling guidebook with cognitive dispute techniques is simultaneous quite effective in increasing self-concept and resilience towards independence students with significance value of 0.020 which is less than 0.05 and an effect size value of 0.485.